Azharists, modernists and orientalists: the intellectual rivalry in Egypt from the late 19th century to the early 20th century - Wang, Ching-Jen (Penerbit Universiti Kebangsaan Malaysia, 2018)
This article aims to study the rather complicated relations and interactions among three major intellectual groups in the late 19th century in Egypt-the Azharists, the modernists and the Orientalists. The Azharists have been the custodians of traditional Islamic values since its establishment in the 10th century. The modernists, however seek to change and either replace or revitalize the unpopular Islamic elements in the society, which were blamed for being the hindrance of progress. The orientalists were not in direct confrontation with the Azharists or the modernists, until they were brought in from Europe to teach in the newly established Egyptian University (later Cairo University) in 1908. The orientalists were favored by many young Egyptians who especially enjoyed the Western scholars’ innovative approaches to knowledge and study. The time frame of this study is set to begin roughly from the time when Muhammad Abduh (1849-1905) was active as a maverick Azharists scholar until the establish of the Muslim Brotherhood in 1928. During this of time, Egyptian society witnessed one of the most vibrant intellectual exchanges and competitions. This article will focus on some of complementary viewpoints on religion, education, history and other subjects, from Egyptian intellectuals and orientalists, such as Muhammad Abduh, Rashid Rida (1865-1935), Taha Husayn (1889-1973), Carlo Nallino (1872-1938), Gaston Maspero (1846-1916), Louis Massignon (1883-1962) among others and demonstrate how the intellectual rivalry at the turn of the century helped transform Egypt into a more diversified and multifaceted society, compared to its neighboring Muslim nations.